Do surprised faces affect infants’ attention toward novel objects? - Höhl, Stefanie; Pauen, Sabina (Neuroreport, 2011)
Previous research has shown that expressions of fear have an effect on infants’ object processing. This event-related potential study addresses the question whether surprised faces affect infants’ brain responses to objects in a similar way, as both expressions share a crucial perceptual feature, wide-opened eyes. Three-month and 9-month-old infants were presented with surprised and neutral faces gazing toward objects. Following each face looking toward an object, the object was presented again without the face. Three-month-olds directed an increased attention to objects that were previously gaze cued by a surprised compared with neutral face as indicated by an enhanced negative central component. This replicates earlier findings using fearful compared with neutral faces as stimuli. Nine-month-olds did not show different responses to objects in both conditions. This suggests that surprised faces have the same effect as fearful faces on 3-month-olds’, but not on 9-month-olds’ object processing. The findings are discussed in terms of social cognitive and visuoperceptual development.
Gesehen am 29.07.2022